Pengaruh Variasi Jumlah Lubang Injektor terhadap Daya Torsi dan Konsumsi Bahan Bakar NMAX: Effect of Variable Number of Injector Holes on Torque Power and NMAX Fuel Consumption - Pande Gede Oka Suarartawan; Nyoman Arya Wigraha; Kadek Rihendra Dantes; Edy Agus Juny Artha (Jurnal Pendidikan Teknik Mesin Undiksha, 2026)
This study aims to analyze the effect of variations in the number of injector holes on power, torque, and fuel consumption on Yamaha NMAX 155 CC motorcycles with Pertamax RON 92 fuel. The study used a quantitative experimental method with a variety of injectors of 4 holes, 6 holes (standard), 8 holes, and 10 holes. The test was carried out using dynotest to obtain engine performance data as well as fuel consumption measurements at various engine revolutions. The results showed that variations in the number of injector holes affected engine power, torque, and fuel consumption. An increase in the number of injector holes tends to increase engine power and torque, but on the other hand fuel consumption also tends to increase. Thus, variations in the number of injector holes have been proven to affect engine performance characteristics and fuel consumption, so the selection needs to be adjusted to the needs of the user, whether it prioritizes improving performance or fuel efficiency. Keywords: Hole injector, power, torque, fuel consumption, Yamaha NMAX 155 CC.